2023
DOI: 10.3389/fimmu.2023.1171145
|View full text |Cite
|
Sign up to set email alerts
|

Construction and validation of a T cell proliferation regulator-related signature for predicting prognosis and immunotherapy response in lung adenocarcinoma

Abstract: BackgroundAs the main executor of immunotherapy, T cells significantly affect the efficacy of immunotherapy. However, the contribution of the T cell proliferation regulator to the prognosis of lung adenocarcinoma (LUAD) and immunotherapy is still unclear.MethodsBased on T cell proliferation regulators, LUAD samples from The Cancer Genome Atlas (TCGA) were divided into two different clusters by consensus clustering. Subsequently, the T cell proliferation regulator (TPR) signature was constructed according to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…Adenosine deaminase (ADA) regulates intracellular adenosine levels, and increased ADA activity is associated with the disease stages of gastric, bladder, breast, colorectal and renal cell carcinoma (Zhulai, et al 2022). Relevant literature has shown that ADA knockout can affect the proliferation, invasion and migration of LUAD, but it has not been veri ed in vivo (Chang, et al 2023). In our study, ADA, as a risk factor for lung adenocarcinoma, was associated with poor clinical outcomes, suggesting that targeting ADA may be a new target for the treatment of LUAD, but its mechanism needs to be further validated and further studied.…”
Section: Discussionmentioning
confidence: 99%
“…Adenosine deaminase (ADA) regulates intracellular adenosine levels, and increased ADA activity is associated with the disease stages of gastric, bladder, breast, colorectal and renal cell carcinoma (Zhulai, et al 2022). Relevant literature has shown that ADA knockout can affect the proliferation, invasion and migration of LUAD, but it has not been veri ed in vivo (Chang, et al 2023). In our study, ADA, as a risk factor for lung adenocarcinoma, was associated with poor clinical outcomes, suggesting that targeting ADA may be a new target for the treatment of LUAD, but its mechanism needs to be further validated and further studied.…”
Section: Discussionmentioning
confidence: 99%